THINKING IN EDUCATION (Author: Matthew Lipman) - Sultana, Ronald G. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1992)
Matthew Lipman. THINKING IN EDUCATION. Cambridge: Cambridge University Press, 1991. 280 pp., 49.50 c1oth, 19.95, paper.